The early and late Roman rural cemetery at Nemesbőd (Vas County, Hungary) - Ilon, Gábor; Kvassay, Judit, 1953- (Archaeopress Roman archaeology, 2015)
The Roman cemetery at Nemesbőd belonged to a settlement or a villa which was located on the territory of the Roman colony of Savaria (present day Szombathey, Hungary) in Pannonia. This book deals with 37 graves, which consisted of mainly cremation but also of some inhumation burials. Detailed analysis of grave goods (bronze vessels, pottery, glass, personal accessories, lamps etc.) provides a study of burial customs and their evolution. In addition, specialist reports on human remains and animal bone as well as on epigraphic material are presented.